(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The chronology of the fixation of the ethnonym Kyrgyz and the beginning of the study of the history of the Kyrgyz people passes an entire epoch. The Kyrgyz, who inhabited the nomadic steppes of Central Asia, were first mentioned in Chinese sources of the 3rd century BC in the writings of historian Sima Qian, which was the first step towards their inclusion in world history. Later, they managed to create a powerful state in Southern Siberia. The study of the history of the Kyrgyz ethnic group is largely related to the industrial revolution that took place in European countries. The need for raw materials for new production methods has contributed to great geographical discoveries. Unexplored territories were discovered, which contributed to the formation of new fields of science aimed at studying the population of these regions and their environment. Initially, the research was conducted in Europe, and later in Russia. Information about the peoples of the Russian state located east of the Ural Mountains was collected in written sources, which aroused the interest of researchers. After Ermak’s campaign in Siberia, it became necessary to collect information about the territory and population of these lands.